THE STUDY OF THE POSITIONING OF A FLEXIBLE MANIPULATOR - Sidyganov, Yuri; Smelik, Victor; Semenov, Konstantin; Kostromin, Denis; Medyakov, Andrey (Journal of Applied Engineering Science, 2018)
The purpose of this paper is a theoretical study of the positioning accuracy of the end part of the developed flexible manipulator. The research was carried out on the basis of its computer and physical models. In the process of computer modelling with the use of Matlab Robotics Toolbox software environment and on the basis of the developed physical model, the principles of determining the position of the end part of a flexible manipulator at known tilt angles of links were set up, taking into account that the geometric dimensions of the models were identical. The results of modelling are presented in the graphs of the coordinate comparison. Based on the results of experiments, we can conclude that, in order to achieve high accuracy of positioning of the end part of a flexible manipulator, it is recommended to avoid the use of cardan joints between the links, or to choose cardan mechanisms with reduced free travel.